Nephron-Sparing Surgery for Renal Cell Carcinoma - Tsui, Ke-Hung (MedReviews, LLC, 1999)
Nephron-sparing surgery has become an established surgical treatment for patients with renal cell carcinoma (RCC), particularly in situations in which preservation of renal parenchyma is critical. However, due to the fear of local renal fossa recurrence with nephron-sparing surgery, radical nephrectomy has historically been the treatment of choice for patients with unilateral RCC and a normal contralateral kidney. Recently, increased incidence of low-stage, localized, solitary RCC has led to renewed interest in partial nephrectomy. With excellent disease-specific survival and recurrence rates comparable to that achieved with radical nephrectomy, nephron-sparing surgery can be confidently utilized in treating patients with stage T1 RCC lesions (<7 cm) and a normal contralateral kidney. The utility of nephron-sparing surgery in the context of adjunctive systemic immunotherapy remains to be explored.